Promt Scaffolding in Learning Life Skills for Self-Development of Intellectual Disabilities Students in Inclusive Primary School - Widajati, Wiwik; Mahmudah, Siti (Jurnal Pendidikan Indonesia, 2022)
Learning life skills for developmentally disabled students who attend inclusive elementary schools is also essential so that students can live independently in their daily activities. The scaffolding prompt plays a vital role in improving the life skills of developmentally disabled students to be independent in their daily activities. This study aims to analyze the relationship and importance of scaffolding prompts in learning life skills for mentally disabled students in inclusive elementary schools. This research was conducted on inclusive elementary school students. This research is a correlational study. The data collection tool used is a self-development performance life skill test which consists of 22 items. The data analysis technique used in this research is the product-moment correlation technique. Based on the research data analysis, there is a significant relationship between scaffolding prompts and improving students' life skills with intellectual disabilities in inclusive elementary schools. The results also show the importance of prompt scaffolding because it contributes significantly to increasing the independence of mentally disabled students in implementing life skills in real-life contexts. The limitation of this research is that it only covers students with mental retardation in inclusive elementary schools, so further research is needed that is broader.